Силова умова сталості процесу холодної тонколистової прокатки - Романюк, Р. Я.; Толок, А. О. (НТУ "ХПІ", 2014)
У роботі проаналiзована рiвновага сил в осередку деформації при холодній тонколистовій прокатці без врахування натягу. Показано, що поряд з контактними втягуючими та виштовхуючими силами необхідно враховувати i сили, які викликані пластичною деформацією металу. Приведені результати теоретичних досліджень по визначенню граничних умов при тонколистовій прокатці без натягу. Проаналiзованi та порівняні вiдомi умови ведення сталого процесу прокатки. Приведені результати досліджень по визначенню граничних умов захвату, виходячи iз заднього натягу, для промислового стану холодної прокатки 1400 при виробництві жерсті

Balance of forces in the byte of deformation is in-process analyses at cold sheet rolling without the tension account. It is shown, that together with contact retracting and expulsive forces it is necessary to consider and forces which are called by a metal flowage. Formulas which allow to find current contact forces and forces of a flowage of metal on known orthographic epures of contact voltages are resulted. Results of theoretical researches by definition limiting conditions are resulted at thin sheet rolling without a tension. On the basis of the given method of consideration of forces, the power condition of conducting resistant to process of cold sheet rolling with a tension and without it is developed. Known conditions of conducting resistant to process of rolling are analyses and compared. Results of researches by definition limiting conditions of capture, proceeding from a back tension, for an industrial camp of cold rolling 1400 are resulted by tin manufacture. Leading-outs are drawn on possibility of application of the developed power condition for definition of stability of process of thin sheet deformation
Power condition of stability process of cold sheet rolling
Keywords: осередок деформації; сила; рівняння рiвноваги; натяг; граничні умови захвату; byte of deformation; force; equilibrium equation; stability; cold sheet of rolling; condition